(untitled) (Journal of the College of Basic Education, 2022)
Perhaps we do not find an author of our critical and rhetorical heritage comparable to ((Critique of Poetry)) by Qudamah Ibn Jaafar 337 (e) in the extent to which he was influenced by the literature of Aristotle, in the level of his intellectual and artistic material, or in his He went far with the principles of logic and inference in drawing the lines of his approach, and he was unique in using philosophical conventions, as it was distinguished by the occurrence of a number of formal concepts of Aristotle, all of which are regulated in